Pusat Pelatihan dan Pertunjukan Seni Tari dan Karawitan Remaja di Kecamatan Tegallalang dengan Pendekatan Arsitektur Biophilic - Dewa Gde Agung Dhiva Pramudya; I Wayan Widanan; I Nyoman Warnata (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2022)
Tegallalang is one of the sub-districts in Gianyar Regency, which has various traditions and cultures that are closely related to social life, especially in the arts. Dance and Karawitan are the most prominent arts in the district of Tegallalang. Empowerment of Youth Resources is used to minimize the occurrence of social deviations in the search for youth identity that goes in harmony with the Customs of Most of the Tegallalang area which makes art as a supporter of social life. In line with this, the facilities and infrastructure to accommodate these activities are not adequate in Tegallalang District and tend to be uneven. Thus, making every activity entitled Culture does not yet have adequate facilities. With Biophilic Architecture, it is hoped that it will be able to answer all the problems between living things and the surrounding environment, so that the site on Jl. Tirtha Tawar-Tegallalang. By using the Bandhurana Concept and the Biophilic architectural theme that embodies a good relationship between the user and the environment which is implemented through zoning, enterance design, patterns and forms of mass according to needs, efficient circulation for the community and air, use of appropriate structures, utilities according to site analysis and local regulations that apply so as to produce designs that are right on target that can harmonize the problems of adolescents in the field of Psychic and Psychic.